International consensus on definition and criteria of borderline resectable pancreatic ductal adenocarcinoma 2017 - Isaji, Shuji; Hackert, Thilo; Michalski, Christoph (Pancreatology, 2018)
This statement was developed to promote international consensus on the definition of borderline resectable pancreatic ductal adenocarcinoma (BR-PDAC) which was adopted by the National Comprehensive Cancer Network (NCCN) in 2006, but which has changed yearly and become more complicated. Based on a symposium held during the 20th meeting of the International Association of Pancreatology (IAP) in Sendai, Japan, in 2016, the presenters sought consensus on issues related to BR-PDAC. We defined patients with BR-PDAC according to the three distinct dimensions: anatomical (A), biological (B), and conditional (C). Anatomic factors include tumor contact with the superior mesenteric artery and/or celiac artery of less than 180° without showing stenosis or deformity, tumor contact with the common hepatic artery without showing tumor contact with the proper hepatic artery and/or celiac artery, and tumor contact with the superior mesenteric vein and/or portal vein including bilateral narrowing or occlusion without extending beyond the inferior border of the duodenum. Biological factors include potentially resectable disease based on anatomic criteria but with clinical findings suspicious for (but unproven) distant metastases or regional lymph nodes metastases diagnosed by biopsy or positron emission tomography-computed tomography. This also includes a serum carbohydrate antigen (CA) 19-9 level more than 500 units/ml. Conditional factors include the patients with potentially resectable disease based on anatomic and biologic criteria and with Eastern Cooperative Oncology Group (ECOG) performance status of 2 or more. The definition of BR-PDAC requires one or more positive dimensions (e.g. A, B, C, AB, AC, BC or ABC). The present definition acknowledges that resectability is not just about the anatomic relationship between the tumor and vessels, but that biological and conditional dimensions are also important. The aim in presenting this consensus definition is also to highlight issues which remain controversial and require further research.